Analyzing Students' Skills in Writing Narrative Texts at SDN Cemorokondang 4 Malang - Rahmayanti, Riszky; Andajani, Kusubakti; Anggraini, Ade Eka (International Journal Labs, 2023)
This study aims to determine the ability to write narrative essays of fifth grade elementary school students. In this study, there are 2 types of narrative essays, namely expository narrative essays and suggestive narrative essays. In this study used a descriptive research method, a qualitative approach. The subjects in this study were 20 students of class V at SDN Cemorokandang 4, Malang City. The instrument used is the instrument for students' ability to write narrative essays. The data analysis technique used is the Milles and Huberman model, which consists of data reduction, data presentation, and verification/conclusion. Based on the results of an analysis of the ability to write narrative essays for fifth grade students at Cemorokandang 4 Elementary School, Malang City, the assessment guidelines for writing narrative essays consist of 6 aspects, namely plot, characters, setting, content, style (choice and vocabulary structure), and spelling and punctuation. The results category for writing expository narrative essays showed 15 students had good criteria, 4 students had enough criteria, and 1 student lacked criteria. The category of students' suggestive narrative writing results showed 2 students with very good criteria, 9 students for good criteria, 3 students for sufficient criteria, and 6 students for poor criteria.